ASSESSMENT OF THE ROLE AND IMPACT OF TNB ON THE WORLD ECONOMY IN THE CONDITIONS OF FINANCIAL GLOBALIZATION - Zelinska , O.M. (The actual problems of regional economy development, 2022)
At the present stage of development of international economic relations and the world economy in general, a key place is occupied by the process of globalization and transnationalization, which has penetrated into all sectors of the world economy, including banking. With the rapid development of globalization processes, the role of transnational banks, which act as intermediaries in international financial markets and take an active part in almost all areas of international economic relations, is growing. The demand for banking operations and the rapid growth of the international capital market give a significant impetus to the expansion of banks outside their home country, creating an extensive branch system in foreign financial markets, combining their links with the banking capital of different countries. The research of issues related to the activities of transnational banks in the globalization of the world economy is covered in the scientific works of both domestic and foreign scholars. The value of scientific papers with their theoretical and practical research is quite high, but issues related to the effectiveness of transnational banks and the regulation of TNB in ​​the homecountries and host countries need further consideration. The study focuses on the world's largest multinational banks. The subject of the study is the activities of the largest multinational banks, which is accompanied by processes of globalization and transnationalization of the world economy. The aim of the article is to analyze the peculiarities of the activities and development of transnational banks, as well as to study their impact on the world economy in the context of globalization and transnationalization. The main research methods used in the study were general philosophical, dialectical, logical-semantic, synthesis method, system-structural, sociological, and statistical method. The most important is the general philosophical method, because the study of transnational processes has its roots in depth, which should be explored with the help of philosophical reasoning. The use of the dialectical method of cognition is due to the ability to explore the problems of TNB in ​​the unity of economic, social, moral and legal content. The method of synthesis provides an opportunity to add new definitions to the categorical apparatus. The results of the study were based on a study of the positive and negative impact of TNB on both the home country and the recipient country. The practical significance of scientific research and its results is the study of the consequences of the inflow of foreign capital and identify situations in which to curb the activities of multinational banks, and in which, on the contrary, to encourage the location of branches of multinational banks in the country.